2021
DOI: 10.1128/spectrum.01162-21
|View full text |Cite
|
Sign up to set email alerts
|

Differences in IgG Antibody Responses following BNT162b2 and mRNA-1273 SARS-CoV-2 Vaccines

Abstract: SARS-CoV-2 vaccines using the mRNA platform have become one of the most powerful tools to overcome the COVID-19 pandemic. mRNA vaccines enable human cells to produce and present the virus spike protein to their immune system, leading to protection from severe illness. Two mRNA vaccines have been widely implemented, mRNA-1273 (Moderna) and BNT162b2 (Pfizer/BioNTech).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 16 publications
7
24
4
Order By: Relevance
“…A higher frequency of the BNT162b2 vaccine was associated with a lower seroconversion rate in IBD patients in the included studies. Our results are in accordance with previous studies 46,47 Therefore, further studies are necessary to evaluate the influence of the country site with the seroconversion rate.…”
Section: Discussionsupporting
confidence: 92%
“…A higher frequency of the BNT162b2 vaccine was associated with a lower seroconversion rate in IBD patients in the included studies. Our results are in accordance with previous studies 46,47 Therefore, further studies are necessary to evaluate the influence of the country site with the seroconversion rate.…”
Section: Discussionsupporting
confidence: 92%
“…The current findings indicate that BNT162b2 and mRNA-1273 both achieve similar peak IgG levels to the SARS-CoV-2 spike RBD antigen following two vaccine doses. Although this finding is at odds with some earlier reports ( 11 , 20 , 21 ), including an interim analysis of the current cohort ( 12 ), it is at least partially explained by different rates of antibody decay that occur following immunization with BNT162b2 and mRNA-1273 and is supported by a recent report from Montoya et al ( 22 ). The detailed kinetic analysis here reveals that IgG levels in recipients of BNT162b2 are dropping markedly (eg, 40%), and to a greater extent than mRNA-1273, as soon as 21 days after the booster immunization.…”
Section: Discussioncontrasting
confidence: 56%
“…Antibody levels were comparable to those recently published in a large cohort of health care workers with mean antibody levels of 760, 688, and 501 BAU/ml after 1, 2, and 3 months, respectively. 7 Our observation of declining antibody levels was further confirmed in six patients where individual follow-up measurements of the vaccination levels were available. Here, all patients except for one (patient #10, Table 1) showed declining antibody levels over time (Figure 1B).…”
Section: Analysis Of the Vaccination-induced Antibody Levels Againstsupporting
confidence: 65%
“…Furthermore, we observed that antibody levels in AA patients declined after second vaccination as previously reported for healthy individuals. 7 For all patients who received a third vaccination, we found a substantial increase in…”
Section: Analysis Of the Vaccination-induced Antibody Levels Againstmentioning
confidence: 75%
See 1 more Smart Citation